Efeitos dos derivados vegetais de condimentos nas características de qualidade e vida de prateleira de linguiça de frango fresca - Barbosa, Lidiane Nunes [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The chicken meat and their subproducts have increased its popularity in recent years due to the development of the sector and the significant changes in the pattern of food consumption. Fresh sausage is probably one of the oldest forms of meat processing, however, is a highly perishable product that requires agents to contribute to the extension of shelf life. Research with natural products of plant origin, especially the spices, has revealed that beyond of the contribution to flavor; these products have antimicrobial and antioxidant activities which could be explored by the food industry. The aim of this study was to evaluate the use of plant derivatives as a possible additive in chicken sausage. Thus, the study was divided into three phases. The first was characterized in vitro antibacterial action (microdilution methodology in Mueller Hinton Broth medium-MHC and determination of minimum inhibitory concentration-MIC) twelve plant derived in the form of essential oils (EOs) and ethanol extracts (Eet) obtained from six plants condiments (laurel-Laurus nobilis, basil- Ocimum basilicum, marjoram-Origanum majorana, oregano-Origanum vulgare, rosemary -Rosmarinus officinalis e thyme-Tymus vulgaris) against nine bacterial strains (Salmonella Enteritidis-ATCC 13076, Escherichia coli O157:H7-ATCC 43895, Pseudomonas aeruginosa –ATCC 27853, Listeria monocytogenes-ATCC 15313, Enterococcus faecalis-ATCC 10100, Aeromonas hydrphila-ATCC 7966, Lactobacillus rhamnosus-ATCC 9595 e Staphylococcus xylosus-ATCC 29979). All plant derivatives showed antibacterial action, however, the activity of Eet was less than the EOs, even when the same plant. T. vulgaris and O. vulgare showed the best activities verified by the MIC values of 1.5 and 1.6 mg/ml for EOs and 2.9 and 4.2 mg/ml for Eet, respectively. The oils of these plants showed thymol as major compound and the extracts were positive for the presence of flavonoids, phenols, triterpenes and steroids. In a ...

A carne de frango e seus subprodutos têm aumentado a sua popularidade nos últimos anos devido ao desenvolvimento do setor e a mudanças significativas no padrão de consumo de alimentos. A linguiça fresca é provavelmente uma das formas mais antigas de processamento de carnes, no entanto, é um produto altamente perecível que necessita de agentes que contribuam para a extensão da sua vida de prateleira. As pesquisas com os produtos naturais de origem vegetal, sobretudo as especiarias, tem revelado que além da contribuição para o sabor, estes produtos possuem atividades antimicrobianas e antioxidantes que poderiam ser exploradas pela indústria de alimentos. O objetivo do trabalho foi avaliar o uso de derivados vegetais como possível aditivo em linguiça de frango. Para tanto, o estudo foi dividido em três etapas. Na primeira foi caracterizada a ação antibacteriana in vitro (metodologia da microdiluição em meio de Mueller Hinton Caldo-MHC e determinação da concentração inibitória mínima-CIM) de doze derivados vegetais na forma de óleos essenciais (OEs) e extratos etanólicos (Eet) obtidos de seis plantas condimentares (louro-Laurus nobilis, manjericão- Ocimum basilicum, manjerona-Origanum majorana, orégano-Origanum vulgare, alecrim -Rosmarinus officinalis e tomilho-Tymus vulgaris) frente a 9 cepas bacterianas (Salmonella Enteritidis-ATCC 13076, Escherichia coli O157:H7-ATCC 43895, Pseudomonas aeruginosa –ATCC 27853, Listeria monocytogenes-ATCC 15313, Enterococcus faecalis-ATCC 10100, Aeromonas hydrphila-ATCC 7966, Lactobacillus rhamnosus-ATCC 9595 e Staphylococcus xylosus-ATCC 29979). Todos os derivados vegetais apresentaram ação antibacteriana, entretanto, a atividade dos Eet foi inferior a dos OEs, mesmo quando da mesma planta. T. vulgaris e O. vulgare apresentaram as melhores atividades verificadas pelos valores de CIM de 1,5 e 1,6 mg/mL para OEs e de 2,9 e 4,2 mg/mL para Eet, respectivamente. Os óleos dessas ...
Keywords: Frango de corte - Subprodutos; Carne - Qualidade; Produtos de ação antimicrobiana; Especiarias; Essencias e oleos essenciais; Meat - Quality